2018
DOI: 10.30681/252610102776
|View full text |Cite
|
Sign up to set email alerts
|

Acidentes por animais peçonhentos na região serrana, Rio de Janeiro, Brasil

Abstract: RESUMO Objetivo: realizar mapeamento epidemiológico sobre os acidentes por animais peçonhentos na Região Serrana do estado do Rio de Janeiro. Método: estudo exploratório e quantitativo, em dados do Sistema de Informação de Agravos de Notificação, analisando os acidentes notificados entre os anos de 2007 a 2015 compreendidos nos municípios da região serrana do estado do Rio de Janeiro. Resultados: os acidentes mais notificados foram causados por serpentes, principalmente Bothrops, seguido dos acidentes por aran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 0 publications
2
4
0
6
Order By: Relevance
“…Studies have shown that the major involvement is in men, the reports varied from 64.85% to 88% of the cases (Feitosa et al 2015;Santos et al, 2017;Roriz et al, 2018;Vieira & Machado, 2018;Oliveira, 2020), corroborating with our finding. Age also varied, Santos et al (2017) reported 56.04% of accidents between 11 and 50 years, and Roriz et al (2018) between 20 and 49 years (75%).…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…Studies have shown that the major involvement is in men, the reports varied from 64.85% to 88% of the cases (Feitosa et al 2015;Santos et al, 2017;Roriz et al, 2018;Vieira & Machado, 2018;Oliveira, 2020), corroborating with our finding. Age also varied, Santos et al (2017) reported 56.04% of accidents between 11 and 50 years, and Roriz et al (2018) between 20 and 49 years (75%).…”
Section: Resultssupporting
confidence: 92%
“…The time that had elapsed between the accident and care being administered, in 66.19% of the cases, was up to 3 hours, which may have contributed to the evolution of cases, with the majority considered cured (89.25%), and only 0.74% of deaths due to snakebites (Table 2). These results corroborated with other studies carried out in Brazil where service time occurred up to 3 hours was associated with mild cases (Bonan et al 2010;Feitosa et al, 2015;Rita et al, 2016 ;Vieira & Machado, 2018;Silva et al, 2020;Oliveira et al, 2020). Roriz et al (2018) observed that the service time was more than 6 hours (72.7%), resulting in 50% of serious cases, the authors reported that the delay occurred due to the distance between the accident site and the center of treatment.…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…De acordo a Organização Mundial da Saúde (OMS), são inúmeros os problemas de saúde pública e acomete, com maior frequência, populações mais vulneráveis que residem em condições precárias. No Brasil, devido ao alto número de notificações, esse agravo foi incluído na Lista de Notificação Compulsória, visando à adoção de estratégias, bem como ações que possibilitem a prevenção desse tipo de acidente (Vieira & Machado, 2018).…”
Section: Introductionunclassified